IMPLEMENTASI PROGRAM 5S (SENYUM, SALAM, SAPA, SOPAN, SANTUN) DALAM MEMBANGUN KARAKTER ISLAMI SISWA MTs PLUS ROUDHOTUL MUHIBIN BEKASI - Slamet Akhiri; Agus Supriyanto (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2020)
This study aims to describe the implementation of the 5S program (Smile, Greetings, Greetings,Politeness, Courtesy) in building the Islamic character of students at MTs Plus Roudhotul MuhibbinBekasi which includes (1) teacher understanding of the nature of Islamic character, (2) 5S programactivities, ( 3) the values contained in the 5S program, (4) the supporting factors, inhibiting factors andefforts to overcome the inhibiting factors of the 5S program. This research uses descriptive qualitativeresearch method of case study. The subjects in this study were school principals, extracurricularteachers, subject teachers and students in grades 7G, 7F, and 7C MTs Plus Rousdhotul MuhibbinBekasi. Collecting data in this study using observations, field notes, interviews, and documents. Thedata analysis process consists of reducing the data, presenting the data and concluding. Checking thevalidity of the data in this study is using triangulation of sources and techniques. The results of thestudy concluded that MTs Plus RMB implemented the 5S program in building the Islamic characterof students. (1) the teacher has understood the nature of Islamic character. (2) the activities of the5S program are carried out in a self-development program which includes routine school activities,spontaneous activities, exemplary, and conditioning, the 5S program is also carried out in subject andextracurricular learning activities. The Islamic values in the 5S program are the values of tolerance,social care, and love of peace. The supporting factors of the 5S program are the presence of teachers,the school environment, and supportive subject matter, the inhibiting factor is the presence of studentswho behave in a disorderly manner and are difficult to regulate.